Alternative fuels: The economic and ecological aspects of their use in the cement clinker firing process - Bibianna Żymła (Economic and Environmental Studies (E&ES), 2018)
A high-temperature process of firing cement clinker in a rotary kiln creates conditions for waste-free thermal waste utilization, in accordance with the EU requirements. The paper presents methods of using waste fuels in the co-combustion process in a rotary furnace as well as types of alternative fuels and methods of their production. Physical and chemical properties of alternative fuels and their impact on the combustion process were characterized. The example of the furnace tested was used to discuss its properties in the co-combustion process of alternative fuels as well as the obtained technical and ecological indicators.
Keywords: O31; P18; P28; Q32; Q42; 330; alternative fuel; co-combustion; cement industry; rotary kiln